REIMAGINING LEARNING DURING THE COVID-19 PANDEMIC WITH EMPHASIS ON PUNISHMENT AND REWARD - Diana Martiani Situmeang (Pusat Riset dan Inovasi Nasional, 2021)
This research aims to find out the extent to which punishment and rewards have an effect on student discipline in the era of online learning. Discipline is an effort to help students develop self-control independently. Discipline will make life orderly, can even regulate behavior and become the basic capital of morality. It is training and guiding a child consistently, and telling him exactly how far he can go. Furthermore, it is explained that discipline means a willingness to obey the rules and stay away from prohibitions. Discipline is something that deals with one's self-control over forms of rules. The application of discipline cannot be separated from the rules as a limit of behavior. Discipline is seen as a process of practice or learning that is concerned with development and growth. What is learned will lead to a way of life so that it can benefit itself and for society This is the moral basis in community life. This research was conducted using quantitative approaches with descriptive methods of correlation. The population distribution in this study was student of Christian education in Tarutung, North Tapanuli, represented by 40 (forty) respondents as sample (N=40). The sampling technique used was random sampling, where all respondents had the same level of probability to fill the questionnaire. Simple regression analysis was used to explore the relationship between the punishment-reward and discipline. The result appears that the correlation that occurs between the two variables is 0.714. Further, it appears that the effect of giving punishment and reward on student’s discipline is 50.9%, while the other 49.1% is influenced by other factors.